XML for browser-based electronic medical records / Maizirah Ibrahim - Maizirah, Ibrahim (2005)
A medical record stores medical history such as diagnosis, results and history of a patient. The patient record is an account of a patient's health and disease after he or she has sought medical help. The record contains findings, considerations, test results and treatment information related to the disease process. Electronic medical record systems should be designed so that they can exchange all their stored data according to public standards. Giving patients control over permission to view their record as well as creation, collation, annotation, modification, dissemination, use, and deletion of the record is the key to ensuring patient's access to their own medical information while protecting their privacy. Many existing electronic medical record systems fragment medical records by adopting incompatible means of acquiring, processing, storing and communicating data. The advantage of representing medical records in XML format would be a platform-independent plain- text forma. Record system should be able to accept data (historical, radio logical, laboratory, etc) from multiple sources including physician's offices, hospital computer systems, laboratories, and patients personal computer. Consumers are managing bank account, investments, and purchases on line, and many turn to the web for gathering information about medical conditions; they will expect this level of control to be extended to online medical portfolios.